2004
DOI: 10.1007/s00701-004-0403-4
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosed giant intracavernous aneurysm with subsequent spontaneous ipsilateral carotid artery occlusion

Abstract: We report a case of a 47-year-old man with a giant thrombosed aneurysm of the right cavernous internal carotid artery who initially presented with headache, double vision and trigeminal numbness. He experienced subsequent asymtomatic proximal occlusion of the parent vessel, revealed by follow-up angiography. This case illustrates the possibility that a giant thrombosed aneurysm may exert enough compression upon the parent vessel to induce flow stasis with resultant intraluminal thrombosis progressing to occlud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 2 publications
1
21
0
Order By: Relevance
“…There was spasm of the parent artery which could have been due to the mass effect of the giant aneurysm leading to stagnation of flow. This has been reported previously in cases of giant intracavernous internal carotid artery aneurysms which thrombosed along with parent artery 14,15 . It has also been pointed out that thrombosis of giant aneurysms is not only due to intraluminal factors but also due to the vessel wall itself.…”
Section: Discussionsupporting
confidence: 71%
“…There was spasm of the parent artery which could have been due to the mass effect of the giant aneurysm leading to stagnation of flow. This has been reported previously in cases of giant intracavernous internal carotid artery aneurysms which thrombosed along with parent artery 14,15 . It has also been pointed out that thrombosis of giant aneurysms is not only due to intraluminal factors but also due to the vessel wall itself.…”
Section: Discussionsupporting
confidence: 71%
“…[4] Alternatively, it may due to sudden expansion of the aneurysm causing compression of the parent artery and resulting in slow flow, with resultant retrograde thrombus formation originating from the aneurysm and extending into the parent vessel. [5] However, in our case, the angiogram was characteristic of a dissection – as evidenced by the presence of the so-called ‘string sign,’ a long segment of narrowed lumen due to lumen occlusion. [8] Hence, we strongly feel that the thrombosis was antegrade rather than retrograde.…”
Section: Discussionmentioning
confidence: 69%
“…The reverse mechanism, i.e., progression from aneurysm thrombosis to parent vessel occlusion, has also been documented. [56] Parent vessel occlusion in the presence of a thrombosed giant carotid artery aneurysm is possibly due to direct distortion, stretching, and compression of the parent artery due to the growth of the aneurysm[14] and consequent compression of the surrounding structures. [4] Alternatively, it may due to sudden expansion of the aneurysm causing compression of the parent artery and resulting in slow flow, with resultant retrograde thrombus formation originating from the aneurysm and extending into the parent vessel.…”
Section: Discussionmentioning
confidence: 99%
“…This can occur at the presentation, as reported in our and most other cases, or on follow-up. Kurokawa et al [7] reported 2 patients, who failed balloon occlusion test for cavernous segment aneurysm, and were followed up and developed [1] 62, F HA, III, IV L MCF Mass Occlusion of ICA Sx Improved Whittle et al, 1982 [4] 27, M HA, Prop, III, IV, VI…”
Section: Discussionmentioning
confidence: 99%